Analysis of Factors Influencing Pharmacist Compliance in Reporting Side Effects of Medications in District Health Center X - Pebrian, Nggio; Hanie Kusuma Wardani; Ardhi Broto Sumanto; Hanik Maria Dewi (Strada Journal of Pharmacy, 2025)
The occurrence of Adverse Drug Reactions (ADR) cases has resulted in an increase in the number of patients experiencing pain and death, both when patients are in the hospital and in everyday life. The purpose of this study was to analyze the factors that influence pharmacist compliance in reporting adverse drug reactions at Health Center X. This study used a quantitative research type with a cross-sectional research design. The study population was all pharmacists at Health Center X with a sample size of 25 respondents. The independent variables were knowledge, attitudes, availability and accessibility, influence of colleagues and rewards, availability of facilities and policies/regulations related to ADR reporting and the dependent variable was practices related to ADR reporting. Data collection used a questionnaire and was analyzed using the Spearman test. From the results of the study, it is known that the significance value of knowledge is 0.351>0.05, the significance value of attitude is 0.545>0.05, the significance value of availability and accessibility is 0.586>0.05, the significance value of availability of facilities is 0.413>0.05, the significance value of ADR reporting policy is 0.127>0.05, meaning that there is no influence between the variables of knowledge, attitude, availability and accessibility, availability of facilities and ADR reporting policy on pharmacist compliance at health centers in District X. While the significance value of the influence of coworkers and rewards is 0.012<0.05, meaning that there is an influence between the variables of the policy of the influence of coworkers on pharmacist compliance at health centers X.